The relationship between torso inclination and the shearing force of the buttocks while seated in a wheelchair: Preliminary research in non-disabled individuals. Issue 6 (1st November 2020) - Shirogane, Satoshi; Toyama, Shigeru; Takashima, Atsushi; Tanaka, Toshiaki
ABSTRACT: The shearing force acting upon the contacting surface of the buttocks while seated in a wheelchair has been linked to the development of pressure ulcers. However, the actual causative factors have not been examined in detail. In an attempt to clarify the nature of this problem, we developed a specific measurement system. In preparation for future clinical applications, we conducted preliminary testing in non-disabled individuals. As a result, we were able to discover a number of issues related to this system and our measurement methods. Although we only evaluated a limited number of typical sitting postures, we were able to record the buttocks shearing force reference values for non-disabled individuals. Our results suggest that regardless of posture, a backward-directed shearing force occurs below the ischial tuberosity in non-disabled individuals in seated positions. This force seemed to increase as the individual leaned forward. Meanwhile, tilting the torso to one side seemed to be associated with an increase in the shearing force working in the opposite direction. We hope that these findings can be utilized for reference purposes in future research among non-disabled individuals.